Penyebab Pengembalian Berkas Klaim BPJS Kesehatan Pasien Rawat Inap Ditinjau Dari Syarat-Syarat Pengajuan Klaim di RSUD Majenang - Tuzzahra, Raudya; Hakim, Agya Osadawedya; Romodon, Dion; Gunawan, Gunawan (Politeknik Negeri Jember, 2024)
Issues related to BPJS Health insurance claims often pose challenges for healthcare facilities. The primary reasons for claim rejections typically involve administrative errors, such as incomplete documentation or incorrect diagnostic codes. This study aims to identify the factors contributing to the high rate of inpatient claim rejections at RSUD Majenang. Employing a qualitative approach with a case study design, this research analyzes data collected from in-depth interviews with hospital verification officers and coding officers. The findings reveal that inaccurate diagnostic coding and incomplete supporting documentation are the primary causes of claim rejections. Inaccurate diagnostic coding is attributed to several factors, including errors in diagnosis recording, discrepancies in perceptions between hospital verifiers and BPJS Health, and potential indications of diagnostic code misuse. Additionally, a lack of interdepartmental coordination and inadequate understanding of claim guidelines contribute to the problem. The findings of this study have significant implications for efforts to improve the quality of healthcare services and the efficiency of claim management in hospitals. To streamline BPJS Health claims, it is necessary to enhance the competency of staff, strengthen interdepartmental coordination, improve the quality of medical documentation, and conduct periodic evaluations of claim procedures.